Chiral resolution of (R,S)-1-phenylethanol using immobilized lipases in batch stirred tank and recirculated packed bed reactors - Chua, Lee Suan (2005)
This study investigated the enantioselective esterification of (R,S)-1- phenylethanol in isooctane. Lauric acid was used as acyl donor in the acyl transfer reaction. Six commercial immobilized lipases; Lipase PS-C, Lipase Sol-Gel-Ak, Chirazyme L2, c.-f., C2, lyo, Chirazyme L2, c.-f., C3, lyo, ChiroCLEC-CR and ChiroCLEC-PC were screened for their resolution activities. Lipases from Pseudomanas cepacia (ChiroCLEC-PC) and Candida antarctica Lipase B (Chirazyme L2, c.-f., C3, lyo) showed higher resolution activities and therefore used in the subsequent study. The kinetic studies were carried out in a batch stirred tank reactor. The enzyme activity and enantioselectivity were determined by varying the enzyme loadings, substrate concentrations from 25 - 250 mM, chain length of fatty acids from C12 – C18, organic solvents with logP value from 1.4 - 4.5, water contents from 0 – 0.5 %v/v and reaction temperatures from 25 – 50 oC. Both enzymes showed the highest activity at the ratio of alcohol to acid 1:3 in isooctane at 35 oC. Both enzymes are also highly selective toward the (R)-enantiomer of 1- phenylethanol with the enantioselectivity value, E > 200. The resolution achieved enantiomeric excess of substrate, ees up to 97 % when molecular sieve 3Å was added into the reaction mixture. A series of reaction progress curves were used to develop the kinetic model using MATLAB. The rate equation was derived based on the principle of mass action law with steady state assumption. The reaction follows Ping-Pong Bi-Bi mechanism with the inhibition of substrates and water. A similar reaction was carried out in a recirculated packed bed reactor. The performance of the enzymes was reduced in this reactor. The decrease was mainly due to poor bed permeability and compaction. A decrease of about 38 – 58 % in term of volumetric productivity was observed as compared to batch stirred tank reactor. However, the productivity of Chirazyme L2, c.-f., C3, lyo (2.74 g/day/g biocatalyst) was much higher than the productivity obtained in the synthesis of (R)-monobenzoyl glycerol (0.94 g/day/g biocatalyst) using the same enzyme in packed bed reactor reported by Xu et al. [246]. The enzymes performance also also reduced in the five fold scaled up reactor compared to the small scale recirculated packed bed reactor. The problems of channelling effect and immobilized enzyme particles compaction exacerbated the enzymes performance in the scaled up of recirculated packed bed reactor.